Internalisasi Nilai Tauhid melalui Pendidikan Islam Berbasis Budaya Lokal pada Anak Usia Dini - Masrurotul Mun’imah; Mohammad Makinuddin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research is motivated by the importance of fostering monotheistic values in early childhood through an Islamic educational approach integrated with local culture. Education is viewed as a discipline that shapes religious life and needs to be integrated with a sense of cultural togetherness to help navigate the increasing tide of globalization. This study aims to provide an overview of Islamic educational values within the process of local cultural acculturation and to explain how children internalize monotheistic values. This research is descriptive and qualitative, using observation, interviews, and documentation as data collection techniques. The results indicate that the values of monotheistic faith, worship, morals, gratitude, trust (relief), and social concern are instilled through role models, familiarization, Islamic stories, and local cultural media such as traditional games, regional songs, and folktales. This study concludes that local culture-based Islamic education is effective in shaping children's religious character while preserving community culture in a contextual, humanistic, and moderate manner